Online Distribution of English-Language TV in Mainland China - Zhang, Xiaoran (2022)
In the age of multiple screens, online video streaming has in the 2010s and present become the most significant way of consuming television content in mainland China. Among all the available content provided by Chinese streaming services, English-language television series stands out as an imported audio-visual product that is mainly distributed and circulated on the internet rather than television channels due to relevant media industry regulations and policies. Prior to landing on online streaming services as its legal distribution platform, English-language television series initially engendered its local audience base via informal distribution means, such as pirated DVDs and file-sharing and downloading websites; yet some of these informal services still exist in a grey area, since the content library formal streaming services possess is largely restricted in terms of size. From the perspective of media industry studies, this thesis deals with both formal and informal distribution platforms with a focus on formal distribution practices and the mechanisms behind them, which involve cultural, political and economic factors. This thesis first examines the streaming services themselves, studying distribution practices for American and British television series to understand the logic behind the localization of the business practices surrounding transnational television and to illustrate the features streaming services adopt to cater to online audiences based on local streaming consumption habits. The thesis then investigates how the current distribution pattern has been constructed by state supervision through cultural policies and censorship and by the historically dynamic relationship between formal distribution and informal distribution. I argue that the localized online distribution of English-language television series in mainland China is the result of the interplay among distributors’ business practices, Chinese authorities’ regulatory practices and Chinese viewers’ consumption habits and viewer practices. Putting the thesis in a global context, I contend that the development of online streaming technologies has created distinctive forms of media consumption in mainland China. Within the specific local political environment, the localized distribution pattern of transnational television content represents part of China’s response to the global television trade.